Perspectives and practices of nutritionists on dietary supplements for elite soccer teams: a cross-sectional survey study - Abreu, Rodrigo; Oliveira, Catarina B.; Brito, João; Teixeira, Vitor H. (Frontiers in Sports and Active Living, 2023)
Introduction and objectives Dietary supplements are part of the nutritional strategies frequently applied in sports performance support. With growing research on this subject and high demand from athletes, nutritionists need to keep up to date with the latest evidence and utility of dietary supplements, particularly in real-world contexts. As information about the use of dietary supplements among elite soccer players is still scarce, this work aimed to know how nutritionists working with elite soccer teams perceive and use these substances in their daily practice. Methods A questionnaire previously used to describe nutritionists’ beliefs and attitudes regarding the use of dietary supplements in a clinical context was adapted for this study. The online questionnaire was addressed to nutritionists working with elite soccer teams from six European Leagues and Brazil, between November 2022 and February 2023. Results Overall, the participants considered themselves well-trained (76.9%), knowledgeable (95.4%), and interested in dietary supplements (95.4%). The majority (70.8%) of the participants agreed or strongly agreed to recommend dietary supplements to soccer players. Personal usage of dietary supplements was associated with recommending supplements (p < 0.001), but no relationships were found with years of experience and academic level. Discussion Nutritionists working with elite soccer players consider the use of dietary supplements for performance-enhancement purposes and not only to compensate for nutritional deficits, which might contribute to their higher interest, training and perceived knowledge about this topic. Participants recognize players’ interest in dietary supplements, and are mindful of the safety and efficacy of these products. The present study suggests that nutritionists working with elite soccer teams are among the highest prescribers of dietary supplements, although personal usage is lower than that of nutritionists working in a clinical context.